Social Networks and the Live Reef Food Fish Trade: Examining Sustainability - Irendra Radjawali (Journal of Indonesian Social Sciences and Humanities, 2011)
This paper employs social network analysis in examining sustainability in the LRFF fishing industry in the Spermonde Archipelago. It is argued that understanding the dynamics of the social networks, which are a result of interactions between different agents with different interests influenced by diverse circumstances (among them are the market, the local social structures, climate variability, biological conditions), is important in coastal fisheries management in general. It is the purpose of this paper to portray the social networks in LRFF fishing in the Spermonde Archipelago and to demonstrate how sustainability in LRFF fishing and trade can be understood through an analysis of these networks. It is the objective of this paper to provide better frameworks for promoting sustainability in reef fishery, particularly in Indonesia, through the elaboration and examination of social networks. In this regard, this paper also aims at providing tools for better coastal and fisheries management.